APPLICATION OF LEARNING MODELS COOPERATIVE TUTORS TO IMPROVE THE ABILITY OF MATHEMATICAL PROBLEMS STUDENT CLASS VIII A SMP NEGERI 1 SUBANG AT MATERIAL LINEAR EQUATION SYSTEM TWO VARIABLES - Imas Mulyasari; Elah Hayati; Warlim Setiawan; Riski Ananda (Journal Of Educational Experts (JEE), 2018)
The mathematical problem-solving ability of SMPN 1 Subang is still low. First, the average of mathematics learning result of grade VIII SMPN students 1 Subang still many who have not reached the value of KKM (KKM = 67). Second, the lesson learned tends to use conventional learning model where the process happens more to the lecture and gives the exercise questions. Third, students tend to be passive, bored, not a few students chatting during the learning process. This study aims to improve the problem-solving skills of mathematics students of class VIII SMP N 1 Subang by using cooperative learning model peer tutor. This research is a Classroom Action Research which passes three cycles with the subject of research is the students of class VIII A of 2017 - 2018 academic year with the number of students 34 people. Instruments of this research are tests on learning outcomes as a test of students' mathematical problem-solving abilities of two- variable linear equation system for initial (before action) tests, cyclical I and II (after action) tests, and observation sheets for teachers and students to conditions of action implementation. The research procedure consists of: (1) planning, (2) implementation of action, (3) observation and evaluation, and (4) reflection. The average value of test results cycle II, ie 65.03 increased by 20.21 compared to the average value of the first cycle test result that is 44.82. And the average value of h acyl test results of the third cycle is 82.26 increased by 17.23. The result of this research can be concluded that the mathematical problem-solving ability of grade VIII A students of SMP N 1 Subang can increase significantly after learning the cooperative model of peer-assisted power point tutor.